2002
DOI: 10.1053/jlts.2002.36740
|View full text |Cite
|
Sign up to set email alerts
|

One hundred consecutive hepatic biopsies in the workup of living donors for right lobe liver transplantation

Abstract: Living donor liver transplantation allows an increasing number of patients with end-stage liver disease the opportunity for effective treatment in the face of a critical shortage of cadaveric organs. Hepatic steatosis decreases functional graft mass and may contribute to graft dysfunction. Screening liver biopsy allows accurate quantitation of hepatic fat, but is an invasive procedure that is not universally employed in the evaluation of living donors. We studied 100 consecutive prospective right lobe living d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
221
1
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(246 citation statements)
references
References 32 publications
13
221
1
11
Order By: Relevance
“…Despite weight loss, no improvements in hepatic steatosis assessed using ultrasonography or in LFTs were noted. However, ultrasonography has been reported to have markedly lower sensitivity when compared to CAP for detecting liver fat, particularly with < 30% liver fat infiltration [38,39]. In contrast, the patients herein displayed reduced liver fat contents, despite no alterations in body composition during the six months.…”
Section: Discussionmentioning
confidence: 62%
“…Despite weight loss, no improvements in hepatic steatosis assessed using ultrasonography or in LFTs were noted. However, ultrasonography has been reported to have markedly lower sensitivity when compared to CAP for detecting liver fat, particularly with < 30% liver fat infiltration [38,39]. In contrast, the patients herein displayed reduced liver fat contents, despite no alterations in body composition during the six months.…”
Section: Discussionmentioning
confidence: 62%
“…Overweight and obese patients are higher-risk living liver donors because of greater likelihood of hepatic steatosis and medical problems (diabetes, hypertension, and heart disease), which could increase the postoperative complications. 12,13 However, recent data have shown that selected obese candidates may successfully undergo donation without evidence of increased complications. 14 Accepted donor candidates were more likely to be related to the recipient (including spouses) than rejected candidates.…”
Section: Discussionmentioning
confidence: 99%
“…In individual patients, especially in tertiary care centres, steatosis should be identified by imaging, preferably US, because it is more widely available and cheaper than the gold standard, MRI (ESM 1 Table 2). US has limited sensitivity and does not reliably detect steatosis when <20% [27,28] or in individuals with high body mass index (BMI) (>40 kg/m 2 ) [29]. Despite observer dependency, US (or computed tomography [CT] or MRI) robustly diagnoses moderate and severe steatosis and provides additional hepatobiliary information, hence it should be performed as a first-line diagnostic test.…”
Section: Liver Biopsymentioning
confidence: 99%